Application of HRAM screening and LC–MS/MS confirmation of active pharmaceutical ingredient in "natural" herbal supplements. (May 2018) - Pascali, Jennifer P.; Fais, Paolo; Vaiano, Fabio; Bertol, Elisabetta
Highlights: Food adulterants is still a problematic issue for consumers' health. An integrated approach by LC-QTOF and LC–MS/MS is proposed with fast sample preparation. Stimulants and anorectic compounds are the most frequently encountered compounds. Dietary supplements composition should be strictly monitored. Abstract: The growing market of herbal remedies worldwide could pose severe problems to consumers' health due to the possible presence of potentially harmful, undeclared synthetic substances or analogues of prescription drugs. The present work shows a simple but effective approach to unequivocally identify synthetic anorectic compounds in allegedly 'natural' herbal extracts, by exploiting liquid chromatography/time of flight (Q-TOF LC/MS) technology coupled to liquid chromatography/triple quadrupole (LC–MS/MS) confirmation and quantitation. The procedure was applied to five tea herbal extracts and pills sold as coadjutant for weigh loss. The method exploited liquid–liquid sample extraction (LLE) and separation in a C18 (2.1 mm × 150 mm, 1.8 μm) column. QTOF acquisitions were carried out both in scan mode and all ion MS/MS mode and results were obtained after search against ad hoc prepared library. Sibutramine, 4-hydroxyamphetamine, caffeine and theophylline were preliminary identified samples. Confirmation and quantitation of the preliminary identified compounds were obtained in LC–MS/MS after preparation of appropriated standards. Sibutramine, caffeine and theophylline were finally confirmed and quantitate.